The Application of Speaking Development on the Establishment of Object Vocabulary in Student with Hearing Impairment - Endang Rusyani; Fauzia Nur Awaliah; Rina Maryanti; Dwi Fitria Al Husaeni; Risti Ragadhita; Budi Susetyo (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to determine the increase in the results of the application of speech development to the formation of object vocabulary in deaf children. The approach used is a quantitative approach with the Single Subject Research (SSR) experimental method in the A-B-A design. The A-B-A design used has three phases: 1) Before the intervention/treatment is given, 2) when the treatment/intervention is given in the form of speech development (B), 3) after the treatment is given (A2). The results of the study showed the mean level of the baseline-1 phase (A-1) 43.43%, the intervention phase 47.07%, and the baseline-2 phase (A-2) 51.48%. Then, in the intervention phase (B) to baseline-1 (A-1), there was a 50% overlap, while in the intervention (B) to baseline-2 (A-2) there was no 0% overlap. Each session experienced an increase, although not significantly. The influence of the intervention on the formation of the object vocabulary of deaf children can still be said to be quite increasing because it has increased both before being treated and after being given treatment. Thus it can be concluded that the application of speech development is sufficient to increase the formation of object vocabulary in deaf children. The application of speech development is very important for deaf children so that deaf children are able to function their speech organs well and so that deaf children are able to communicate with other people, both the implementation of speech development is carried out in class or providing additional classes outside of class hours.